2018
DOI: 10.1557/jmr.2018.407
|View full text |Cite
|
Sign up to set email alerts
|

The delayed degradation mechanism and mechanical properties of β-TCP filler in poly(lactide-co-glycolide)/beta-tricalcium phosphate composite suture anchors during short-time degradation in vivo

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…4(a) , the PLGA diffraction peak was located at 2θ = 10–26.47°. 26 The relevant MBG diffraction peaks at 2θ = 15°–35° were identifiable in PLGA–MBG and PLGA–MBG–Sim composites. 27 In PLGA–MBG–Sim composites [ Fig.…”
Section: Resultsmentioning
confidence: 95%
“…4(a) , the PLGA diffraction peak was located at 2θ = 10–26.47°. 26 The relevant MBG diffraction peaks at 2θ = 15°–35° were identifiable in PLGA–MBG and PLGA–MBG–Sim composites. 27 In PLGA–MBG–Sim composites [ Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Some of the vital factors to be considered are morphology, aperture, porosity, and spatial orientation. The right amount of pore size is advantageous toward promoting cell attachment, migration, proliferation, differentiation, and finally bone regeneration [ 52 ]. Technical issues can affect biomaterial functionality [ 32 ] and can potentially alter the microenvironment relative to the scaffold, thereby causing cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that PLGA has many advantages along with some disadvantages. The toughness of pure PLGA is poor, the mechanical strength of it cannot meet the requirements of loadbearing site applications, the poor cell attachment ability and bioactivity [18], and the degradation products are acidic, which is not conducive to the formation of new bone [19,20].…”
Section: Introductionmentioning
confidence: 99%